Cross-correlation of plasma concentrations of branched-chain amino acids: A comparison between healthy participants and patients with chronic kidney disease. (August 2020) - Ikeda, Hideki
Summary: Background & aims: Plasma concentrations of branched-chain amino acids (BCAAs) are known to exhibit strong intercorrelations; however, the associated regulatory mechanism is not sufficiently understood. Furthermore, the mechanisms underlying the intercorrelation changes in metabolic disorders with the disease are unclear. Therefore, plasma BCAAs in patients with chronic kidney disease (CKD) were examined. Methods: This study included a healthy group of older participants (Group C; n = 87, 46 males, 41 females) who had undergone health examinations at Sanyudo Hospital and a group of CKD patients (Group CKD; n = 71, 49 males, 22 females) receiving maintenance hemodialysis at the same hospital. Samples from Group C were collected 12 h after fasting. CKD samples were collected before and after hemodialysis (pre-HD and post-HD, respectively), without 12 h fasting. The samples were analyzed for 38 amino acids by SRL Inc., using liquid chromatography-mass spectrometry (LC-MS). Results: Differences between the plasma BCAA concentrations of Group C and pre-HD were determined. Dialysis-induced BCAA losses were different for each BCAA. However, strong intercorrelations between the plasma concentrations of each BCAA were maintained. In addition, the regression lines did not converge at the origin and were in different positions for groups C, pre-HD, and post-HD. A different distribution of the constant ( b ) for each group was observed for each BCAA correlation when a in the regression line (Y =  a X +  b ) was fixed at the value for Group C, and b was calculated. Conclusion: Strong intercorrelations among plasma concentrations of BCAAs were maintained in CKD patients both pre- and post-dialysis, whereas the changes in the plasma concentrations of each BCAA were different. We speculate that there is a novel mechanism that selectively regulates each BCAA and suggest that changes in the constant of the regression formula for correlation may have a novel function as an index for renal contribution to BCAA metabolism.